1. The problem statement, all variables and given/known data Prove that sin(5A)+sin(2A)-sin(A) = sin(2A)*(2*cos(3A)+1) 2. Relevant equations sin(2A) = 2(sin(A)cos(A)) cos(2B) = cos2(A)-sin2(A) cos(A+B) = cos(A)cos(B) - sin(A)sin(B) sin(A+B) = sin(A)cos(B) + sin(B)cos(A) 3. The attempt at a solution I can't find any other way than to just decompose the whole thing into sinA or cosA, and that is really long and usually full of mistakes. Is there something that i'm missing here? Something that makes this proof a lot easier?